Assessment of somaclonal variation in chrysanthemum (Dendranthema grandiflora Kitam.) using RAPD and Morphological analysis - P. Kengkarj (2018)
Novel chrysanthemum (Dendranthema grandiflora Kitam.) somaclones from seven commercial cultivars were obtained through the petal segments culture. Morphological variation of the derived clones observed from the field trials was found to be cultivar specific. The major variants within the same cultivar were found only color and inflorescence shape deviation, whereby leaf and stem characters remained unchanged. Distinct variations were found in the 'Pinkgin' cultivar that color changed from magenta to red. The morphological differences of the tested somaclones showed high correlation with the RAPD patterns analysis. The morphological differences of the tested somaclones were shown to be highly correlated using RAPD pattern analysis. RAPD markers, using ten primers could better separate each cultivar at 80% similarity value. All the somaclones could be singly separated at 90% similarity. However, the higher level of variability of RAPD patterns in chrysanthemum rendered these RAPD fragments as good candidates for somaclonal and cultivar identification. The results from this study revealed the potential increase in range of floral color and morphological changes of petal segment culture, thus this technique would be effectively used for novel plant production.